The left ventricular outflow tract and carotid artery velocity time integrals - Kenny, Jon-Emile S. (Frontiers in Medical Technology, 2024)
The left ventricular outflow tract velocity time integral (LVOT VTI) is commonly used in the intensive care unit as a measure of stroke volume (SV) and how the SV changes in response to an intervention; therefore, the LVOT VTI is used to guide intravenous fluid management. Various peripheral Doppler surrogates are proposed to infer the LVOT VTI (e.g., measures from the common carotid artery). A recently-described, novel method of insonation has an excellent ability to detect change in the LVOT VTI. This approach raises important facets of Doppler flow and insonation error, as well as the general principles at play when using a peripheral artery to infer changes from the left ventricle. Relating the VTI of a peripheral artery to the LVOT VTI was recently described mathematically and may help clinicians think about the Doppler relationship between central and peripheral flow.